1) 1.8(2х+1)+1=3(4х-2)-1=
16x+8+1=12x-6-1
16x+8+1-12x+6+1=0
4x+16=0
4x=-16/4
x=-16/4=-4/1=-4
2.8(2x+1)+1=3(4x-2)-1=8(2*(-4)+1)+1=3(4*(-4)-2)-1=8(-8+1)+1=3(-16-2)-1=-64+8+1=-48-6-1=-64+8+1+48+6+1=-64+64=0
2) 1. 0,3(8-3x)=3,2-0,8(x-7)=0
2,4-0,9x=3,2-0,8x+5,6
2,4-0,9x-3,2+0,8x-5,6
-0,1x-6,4=0
-0,1x=6,4/(-0,1)
x=-64
2. 0,3(8-3(-64))=3,2-0,8(-64-7)=0,3(8+192)=3,2-0,8(-64-7)=2,4+57,6=3,2+51,2+5,6=2,4+57,6-3,2-51,2-5,6=60-60=0
3) 1. 9(3x-2)-6=5(4x-1)+2=
27x-18-6=20x-5+2
27x-18-6-20x+5-2
7x-21=0
7x=21/7
x=3
2. 9*(3*(3)-2)=5*(4*(3)-1)+2=9(9-2)-6=5*(12-1)+2=81-18-6=60-5+2=81-18-6-60+5-2=86-86=0
4)0,2*(7-2x)=2,3-0,3(x-6)=0
1,4-0,4x=2,3-0,3x+1,8
1,4-0,4x-2,3+0,3x-1,8
-0,1x-2,7=0
-0,1x=2,7/(-0,1)
x=-27
2. 0,2(7-2*(-27))=2,3-0,3(-27-6)=0,2(7+54)=2,3-0,3(-27-6)=1,4+10,8=2,3+8,1+1,8=1,4+10,8-2,3-8,1-1,8=12,2-12,2=0
5) 1. 10y+2(7y-2)=5(4y+3)+3y=0
10y+14y-4=20y+15+3y
10y+14y-4-20y-15-3y
y-19=0
y=19/1
y=19
2. 10*19+2(7*(19)-2)=5*(4*(19)+3)+3*19=190+2(133-2)=5(76+3)+57=190+266-4=380+15+57=190+266-4-380-15-57=456-456=0